PENGARUH SUKU BUNGA TERHADAP VOLUME TABUNGAN SIMPEDES NASABAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk. CABANG BULUKUMBA - Fitrianti, A Nur; Peteransah, Nufadillah (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
This study aims to determine the effect of interest rates on the volume of savings deposits customers at PT. BRI (Persero) Tbk Branch of Bulukumba.The population in this study is the interest rate and all the amount of savings customers. While the sample used is the interest rate from 2008-2014 and the amount of customer savings for 6 (six) years. Technique of data collecting done by observation, documentation, further analysis technique used is simple regression and correlation technique. The results of this study indicate that there is a very strong relationship and direction between the interest rate with the volume of savings at PT. BRI (Persero) Tbk in the city of Bulukumba with nilia (r = 0.84) and the influence of the interest rate on the saving volume is significant, since the tcount (4.2) is greater than the ttable on degrees of freedom 4 (2.13). Hence the hypothesis proposed earlier states that there is a significant influence between the interest rate with the volume of customer savings at PT. BRI (Persero) Tbk Branch Bulukumba for the last 6 (six) years (2008-2014) proved.